Association of Xerostomia and Assessment of Salivary Flow Using Modified Schirmer Test among Smokers and Healthy Individuals: A Preliminutesary Study - Dyasanoor, Sujatha (JCDR Research and Publications (P) Limited, 2014)
Background and Objective: Several oral diseases such as dental caries, periodontitis and oral infections can be a major concern in patients suffering from mouth dryness. Whole mouth salivary flow is affected by many factors which may include habits like smoking. The aim of the present study was to investigate the incidence of xerostomia and hyposalivation among smokers. Materials and Methods: The study groups included 60 smokers and 60 healthy non-tobacco users as case and control groups respectively. A questionnaire was used to collect the smoking habits and symptoms associated with xerostomia. Measurement of unstimulated whole mouth salivary flow for 3 minutesutes was performed using modified Schirmer test. The results were subjected to statistical analysis. Results: The prevalence of xerostomia symptom was 37% in smokers and it was 13% in non-smokers, with a statistically significant difference between groups (p=0.003). The prevalence of hyposalivation was 43% in smokers, whereas it was only 8% in the control group (p< 0.001). Conclusion: Xerostomia symptoms with significant reduction in unstimulated whole mouth salivary flow were associated with long term smoking.